Histological study of the development and sex differentiation of the gonad in the European eel - COLOMBO, Giuseppe; GRANDI, Gilberto (Journal of Fish Biology, 1996)
The histological structure of the gonads was studied in yellow eels sampled from a coastal lagoon and from stocks reared in an aquaculture plant showing different sex ratios. Gonad development related to body size rather than to age and underwent an intermediate stage characterized by a structure of an early testis but containing oogonia and oocytes. This gonad was called the Syrski organ and the stage juvenile ambisexual. Ovaries were found in eels from 22-30 cm in length, possibly derived from undifferentiated gonads or from Syrski organs. Fully differentiated testes were found in eels >35 cm, derived from Syrski organs. These observations support the results of previous research. From elvers and in eels up to 15-16 cm in length, growth of the gonadal primordium is due to primordial germ cell migration. In eels > 15 cm multiplication of primordial cells begins. Oogonial clones were found in eels > 18 cm in length, while spermatogonium B clones were observed in eels >30 cm in length. The dynamics of sex differentiation was different among stocks with different ultimate sex ratios: ovaries were found in shorter eels in stocks with a prevalence of females, in longer eels in stocks with a prevalence of males. This result supports the hypothesis of a metagametic (environmental) sex determination. The somatic cells in contact with germ cells and those in the interstitium appeared early during gonad development and preceded germ cell differentiation. This suggests that somatic cells are the targets of the environmental factors influencing sex differentiation.